The Influence of Environmental Cost Disclosure, Environmental Performance, and Corporate Social Responsibility (CSR) on the Profitability of Manufacturing Companies in the Basic and Chemical Industry Sector Listed on the IDX in 2020–2024 - Khadijah, Adila; Yuliandhari, Willy (SAFE-Network, 2025)
This study aims to analyze the influence of environmental cost disclosure, environmental performance, and corporate social responsibility (CSR) on company profitability. The research focuses on manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The research method employed is multiple regression analysis to examine the relationship between the independent variables (environmental cost disclosure, environmental performance, and CSR) and the dependent variable (profitability, measured using the Return on Assets (ROA) ratio). The data used in this study were obtained from the annual reports of manufacturing companies listed on the IDX from 2020 to 2024. The findings of this study are expected to provide insights for companies in improving environmental management practices and CSR activities that can support sustainable financial performance. In addition, the results are also expected to serve as a consideration for regulators and other stakeholders in formulating policies related to corporate sustainability in Indonesia. The results of the study indicate that CSR is the most dominant variable in enhancing company profitability, while environmental cost and environmental performance play a more long-term role as efforts to maintain business sustainability.